Effects of dietary intervention on vitamin B12 status and cognitive level of 18-month-old toddlers in high-poverty areas: a cluster-randomized controlled trial - Xiaoyang Sheng; Junli Wang; Feng Li; Fengxiu Ouyang; Jingqiu Ma (BMC, 2019)
Abstract Background The local diet in high-poverty areas in China is mainly vegetarian, and children may be more vulnerable to vitamin B12 deficiency. Objective The aims of this study were to explore the vitamin B12 status of toddlers living in high-poverty areas of China and to observe the effects of different complementary foods on the vitamin B12 status and cognitive level of these toddlers. Methods The study was nested within a cluster-randomized controlled trial implemented in 60 administrative villages (clusters) of Xichou County in which infants aged 6 months old were randomized to receive 50 g/d of pork (meat group), an equi-caloric fortified cereal supplement (fortified cereal group) or local cereal supplement (local cereal group) for one year. At 18 months, a subsample of the 180 toddlers (60 from each group) was randomly tested for serum vitamin B12 and total homocysteine (tHcy) levels, and their neurodevelopment was evaluated. Results The median serum concentrations of vitamin B12 and tHcy were 360.0 pg/mL and 8.2 μmol/L, respectively, in children aged 18 months. Serum vitamin B12 concentrations less than 300 pg/mL were found in 62 (34.4%) children, and concentrations less than 200 pg/mL were found in 30 (16.7%) children. The median vitamin B12 concentration was significantly different among the three groups (P < 0.001). The highest vitamin B12 level was demonstrated in the fortified cereal group (509.5 pg/mL), followed by the meat group (338.0 pg/mL) and the local cereal group (241.0 pg/mL). Vitamin B12 concentration was positively correlated with the cognitive score (P < 0.001) and the fine motor score (P = 0.023) of the Bayley Scales of Infant Development, 3rd Edition (BSID III) screening test. Compared to the local cereal group, children in the meat group had higher cognitive scores (P < 0.05). Conclusion In poor rural areas of China, vitamin B12 deficiency in toddlers was common due to low dietary vitamin B12 intake. Fortified cereal and meat could help improve the vitamin B12 status of children and might improve their cognitive levels. Trial registration The larger trial in which this study was nested was registered at clinical trials.gov as NCT00726102. It was registered on July 31, 2008.